Lessons from the New Deal: Did the New Deal prolong or worsen the Great Depression? - Greg Hannsgen; Dimitri B. Papadimitriou (Levy Economics Institute of Bard College, 2009)
Since the current recession began in December 2007, New Deal legislation and its effectiveness have been at the center of a lively debate in Washington. This paper emphasizes some key facts about two kinds of policy that were important during the Great Depression and have since become the focus of criticism by new New Deal critics: (1) regulatory and labor relations legislation, and (2) government spending and taxation. We argue that initiatives in these policy areas probably did not slow economic growth or worsen the unemployment problem from 1933 to 1939, as claimed by a number of economists in academic papers, in the popular press, and elsewhere. To substantiate our case, we cite some important economic benefits of New Deal-era laws in the two controversial policy areas noted above. In fact, we suggest that the New Deal provided effective medicine for the Depression, though fiscal policy was not sufficiently countercyclical to conquer mass unemployment and prevent the recession of 1937-38; 1933's National Industrial Recovery Act was badly flawed and poorly administered, and the help provided by the National Labor Relations Act of 1935 came too late to have a big effect on the recovery.
Keywords: E20; E62; J58; L43; N12; 330; New Deal; public works projects; NIRA; NLRA; cartelization; unions; labor relations policy; fiscal policy; fiscal stimulus; unemployment; Great Depression